2m(3+4m)+4m=

Simple and best practice solution for 2m(3+4m)+4m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m(3+4m)+4m= equation:


Simplifying
2m(3 + 4m) + 4m = 0
(3 * 2m + 4m * 2m) + 4m = 0
(6m + 8m2) + 4m = 0

Reorder the terms:
6m + 4m + 8m2 = 0

Combine like terms: 6m + 4m = 10m
10m + 8m2 = 0

Solving
10m + 8m2 = 0

Solving for variable 'm'.

Factor out the Greatest Common Factor (GCF), '2m'.
2m(5 + 4m) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0

Subproblem 2

Set the factor '(5 + 4m)' equal to zero and attempt to solve: Simplifying 5 + 4m = 0 Solving 5 + 4m = 0 Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 4m = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 4m = 0 + -5 4m = 0 + -5 Combine like terms: 0 + -5 = -5 4m = -5 Divide each side by '4'. m = -1.25 Simplifying m = -1.25

Solution

m = {0, -1.25}

See similar equations:

| 12(x-4)-3=19x-100 | | 0.1t=0.6+0.5t | | A=L(W) | | -9(-7n+1)=-8+4(4n-12) | | -346x=0 | | 125x^3-20x=0 | | 6x-15=x+15+5x | | 100+10j=15j | | 9t+9-3t-7= | | 0=y^2+10y+9 | | 3x-5=7x+x-15 | | 9-4w=-11 | | 5(1+4h)+2h=27 | | 12k+9m-2m-12k= | | 5a+2=3a+2 | | 3+2x=14-3x | | 35.00+0.75x=1.25x | | 3x+16=5-x | | 5h^2-15h-270= | | 2x+3+51=180 | | 2-6(z+1)=4(z-2)+10 | | 2s^2-128= | | 5(3b-5)=4(6b-2) | | 2x+3y=7800 | | 3+4x-3=13 | | 12a+3=25 | | 25+8x=7 | | -16=7[p+3]+30 | | 10t+15-10-6t= | | -12(10-11x)=-6(x-3) | | 210+10+400+x=1000 | | 4x-7+1=8 |

Equations solver categories